Estimation of Pressure Propagation during Hydraulic Stimulation Based on Micro-seismic Events - OSADA Kazuyoshi; ITO Takatoshi; HAYASHI Kazuo; BARIA Roy (Journal of the Geothermal Research Society of Japan, 2005)
In the hydraulic stimulation, massive fluid is injected into subsurface rock through drilled wells. Then a number of micro-seismic events are commonly observed. By analyzing the data of microseismic event associated with hydraulic stimulation, we can estimate the orientation, i.e. dip and strike, of the fracture which slides to induce micro-seismic event. From the estimated orientation taking into account the in-situ stresses and the Mohr-coulomb criterion to describe the critical condition of fracture sliding, we can estimate the pore pressure at the location of sliding fracture and at the time when the sliding occurs, in other words, when micro-seismic event occurs. The estimated values of pore pressure are sorted in a certain manner for each equally-divided spatial region, i.e. block, to give spatial distribution of pore pressure and its variation with time during hydraulic stimulation. For an example, we applied this method to the micro-seismic data observed during the hydraulic stimulation performed in September 1993 at Soultz field in France. We obtained successfully the estimated pore pressure distribution.